MORPHOLOGICAL DESCRIPTION OF MEDINILLA SPP. IN BALI BOTANIC GARDEN IN ORDER TO DEVELOP AS ORNAMENTAL PLANT - I Nyoman Peneng; Wayan Sujarwo (Widyariset, 2011)
The morphological description of 13 species of Medinilla spp. (Melastomataceae) in Bali Botanic Garden has been conducted based on morphological characters, so that it could be evidence to be justifi ed as ornamental plant. The study was conducted on plant collections of Bali Botanic Garden and the species of Medinilla which is growing wild inside the garden. Morphological data and agronomic potential of each species were showed in order to support its development as ornamental plant. Based on the results of observation of morphological characterization,several species of Medinilla was suitable to be developed as ornamental plant in pots or planted directly in the fi eld. Further explanation of each Medinilla as ornamental plant will be discussed in this paper.